Economic Policy
DOI: 10.1002/9781444307238.ch2
|View full text |Cite
|
Sign up to set email alerts
|

From Individual Attitudes towards Migrants to Migration Policy Outcomes: Theory and Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
1

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 15 publications
(17 reference statements)
5
111
1
Order By: Relevance
“…The heads of the supermarket chain Sainsburys and the head of the European division of the investment bank Merrill Lynch were among the signatories. 16 See, for example, Facchini and Mayda (2008). This paper's results are consistent with the fact that, in recent years, U.S. labor unions have substantially toned down the rhetoric against migration.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…The heads of the supermarket chain Sainsburys and the head of the European division of the investment bank Merrill Lynch were among the signatories. 16 See, for example, Facchini and Mayda (2008). This paper's results are consistent with the fact that, in recent years, U.S. labor unions have substantially toned down the rhetoric against migration.…”
Section: Introductionsupporting
confidence: 77%
“…), by performing a falsification exercise and, finally, by using an instrumental-variable estimation strategy. Facchini and Mayda (2008) focus, instead, on cleavages across occupation/skill lines, rather than across sectors. Using a panel covering the period 1994-2005 and differentiating labour according to both skill levels and occupations, the paper finds systematic evidence suggesting that the lobbying activity of organized labour leads to a reduction in the inflow of foreign workers in the same occupation/education cell -this effect is driven by substitutability -and to an increase in the inflow of foreign workers in different occupation/education cells -this effect is driven by complementarity.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Studies by both Nisbet (2005) and Ho, Brossard, and Scheufele (2008) illustrated that ideology was a significant predictor of support for stem cell research. Finally, Facchini and Mayda (2008) found that "political affiliation with the right" was negatively correlated with immigration reform opinions allowing for more open borders. The studies by Hicks and Lee, and Haider-Markel and Joslyn were explanatory studies, utilizing advanced statistical modeling techniques.…”
Section: Factors In the Proposed Studymentioning
confidence: 99%